Characterization for the transformation of dissolved organic matters during ultraviolet disinfection by differential absorbance spectroscopy. (March 2020) - Wu, Hao; Chen, Zhanghao; Sheng, Feng; Ling, Jingyi; Jin, Xin; Wang, Chao; Gu, Cheng
Abstract: The transformation of dissolved organic matter (DOM) during various disinfection processes has raised great concerns due to the generation of carcinogenic disinfection by-products (DBPs). Ultraviolet (UV) irradiation is an effective method for drinking water disinfection, during which DOM undergoes changes in functional groups and molecular weight. In this study, the spectrophotometric titration and gel permeation chromatography (GPC) determination were employed to investigate the changes in oxygenated groups and weight-averaged molecular weight ( M w ) of two typical DOM during UV irradiation. The differential absorbance spectra (DAS) of DOM could be deconvoluted into six Gaussian bands. The change of relative band intensity was attributed to the change of oxygenated groups (carboxylic and phenolic groups), which was confirmed by combining DAS data and revised Non-Ideal Competitive Adsorption -Donnan model. The GPC result demonstrated that the M w of DOM decreased after UV disinfection. Moreover, a linear correlation between M w and the intensity of deconvoluted Gaussian band from DAS was established, which might be served as an alternative approach to estimate M w and predict the hydrophobicity and DBPs formation potential of DOM in drinking water treatment and monitoring. Graphical abstract: Image 1 Highlights: DAS method is applied to evaluate the change of DOM after UV disinfection. Gaussian bands deconvoluted from DAS spectra reveal the change of carboxylic and phenolic groups. Relative contents of oxygenated groups are estimated by revised NICA-Donnan model. A linear relationship between M w and DAS parameter of DOM is developed.